A STRATEGI KOMUNIKASI STARBUCKS SIGNING STORE DALAM MENGATASI KESENJANGAN INTERAKSI DAN KOMUNIKASI ANTARA TEMAN TULI DENGAN TEMAN DENGAR - Alya Fauziah Nursyifa; A. Hasan Al Husain; Wa Ode Seprina (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2024)
Employment opportunities for people with disabilities in Indonesia remain a major issue. Only 720,748 out of 22.97 million people with disabilities were employed in 2022, demonstrating the limited job opportunities for this group. The presence of Starbucks Signing Store has created job opportunities for individuals who are deaf. This study aims to understand the communication strategies used by Starbucks Signing Store in bridging the interaction gap between deaf and hearing individuals. The research employs a qualitative method with a case study approach. The findings indicate that the communication strategies used to address the communication gap between deaf and hearing individuals include identifying communication targets, selecting appropriate communication media, evaluating the purpose of communication messages, and the role of communicators in the communication process. Keywords: Employment Opportunities for Disabilities, Starbucks Signing Store, Communication Strategies, Deaf Individuals, Hearing Individual